CdSe/V2O5 core/shell quantum dots decorated reduced graphene oxide nanocomposite for high-performance electromagnetic interference shielding application. (27th September 2019) - Singh, Ashwani Kumar; Yadav, Amar Nath; Srivastava, Amit; Haldar, Kamal Krishna; Tomar, Monika; Alaferdov, Andrei V; Moshkalev, Stanislav A; Gupta, Vinay; Singh, Kedar
Abstract: The present work reports nanocomposite of CdSe/V2 O5 core–shell quantum dots with reduced graphene oxide (rGO-V-CdSe), as an efficient lightweight electromagnetic wave shielding material, synthesized by a simplistic solvothermal approach. The as-synthesized nanocomposite was analyzed for its structural, compositional and morphological features by x-ray diffraction (XRD), transmission electron microscopy (TEM), Raman spectroscopy and x-ray photoelectron spectroscopy (XPS). The measurement of complex permittivity/permeability and total shielding efficiency of the as-synthesized samples has been done in a wide frequency range of 8–12 GHz (X-band). Compared to rGO and rGO-CdSe, rGO-V-CdSe nanocomposite exhibits significantly enhanced EMI shielding properties in terms of both dielectric loss and total shielding SE T . The high value of real permittivity (average ε ′∼70) and the overall shielding effectiveness up to ∼38 dB have been recorded for rGO-V-CdSe nanocomposite. The studies also infer that the absorption contributes more in total shielding than reflection. The high value of dielectric loss and shielding effectiveness could also be attributed to the presence of various defects leading to dipolar and interfacial polarizations. The excellent EMI shielding properties of the nanocomposite in GHz frequency range (X-band) pave an intuitive way for fabricating a versatile EMI shielding nanocomposite material for applications.